EFFECTIVENESS OF CONSUMPTION OF BANANA KEPOK HEART VEGETABLES ON FLOWNESS MILK PRODUCTION IN BREASTFEEDING MOTHERS IN TPMB MURNI - Farlikhatun, Lili; Barus, Murni Natalia (HEARTY, 2024)
Background: In 2020 UNICEF reported that the average coverage of exclusive breastfeeding in the world for babies aged 0-6 months only reached 38%. Exclusive breastfeeding in developing countries can prevent 90% of under-five deaths due to diarrhea and acute respiratory infections. Exclusive breastfeeding coverage in Indonesia is 52%, in Banten Province it is 72.6%, and in Pandeglang it is 70.93%. Low coverage of exclusive breastfeeding can be caused by various factors, one of which is not optimal breast milk production. The impact of breast milk not flowing smoothly makes mothers think about taking steps to stop breastfeeding and replace it with formula milk. One way to speed up breast milk production is by consuming boiled kepok banana blossoms which can increase breast milk production. The results of a preliminary study conducted at TPMB Murni found that 6 breastfeeding mothers had problems with breast milk production which was not smooth so they switched to formula milk. Research Objective: To determine effectiveness Consumption of kepok banana flower vegetables on the smooth production of breast milk in breastfeeding mothers. Research Method: Quasi experimental with one group pretest-posttest design research type. The sample in this study was all postpartum mothers at TPMB Murni in November 2023, totaling 30 people, the sampling technique was total sampling. Research Results: Frequency distribution of smooth breast milk production before consuming the Kepok banana flower vegetable was mostly substandard at 56.7%, and after consuming the Kepok banana flower vegetable the majority was smooth at 63.3%. Kepok banana flower vegetables can effectively increase the smooth production of breast milk in breastfeeding mothers at TPMB Murnim in 2023 ( p value 0.000). Conclusions and Suggestions: Kepok banana flower vegetables can effectively increase the smooth production of breast milk in breastfeeding mothers at TPMB Murnim in 2023. It is hoped that midwives will be more active in providing counseling to breastfeeding mothers to consume lots of vegetables and fruit to increase breast milk production.